2017
DOI: 10.1016/j.jss.2017.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of different types of stem cells in preserving gut barrier function in necrotizing enterocolitis

Abstract: Background Necrotizing enterocolitis (NEC) is a leading cause of morbidity and mortality in premature infants. Increased intestinal permeability is central to NEC development. We have shown that stem cells (SC) can reduce the incidence and severity of NEC. Our current goal was to investigate the efficacy of four different types of SC in preservation of gut barrier function during NEC. Materials and Methods We compared: (1) amniotic fluid-derived mesenchymal SC (AF-MSC); (2) bone marrow-derived MSC (BM-MSC); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…The cost of treating infants with NEC exceeds $1 billion in the US each year [2]. Babies who survive NEC frequently have long term complications including short bowel syndrome, developmental delays and neurological sequelae [1][2][3]. Unfortunately, despite much research over the past decades, a cure has not been identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of treating infants with NEC exceeds $1 billion in the US each year [2]. Babies who survive NEC frequently have long term complications including short bowel syndrome, developmental delays and neurological sequelae [1][2][3]. Unfortunately, despite much research over the past decades, a cure has not been identified.…”
mentioning
confidence: 99%
“…Previous research has demonstrated that different types of stem cells (SC) have the ability to reduce the incidence and severity of experimental NEC. Furthermore, extracellular vesicles (EVs) derived from SC are similarly protective against NEC, suggesting that they mediate the therapeutic effects of the SC from which they originate [1,2]. EVs are nanovesicles,~20-200 nm in size, that are released by many cells in the body and are ubiquitously present in body fluids including saliva, urine, and breast milk [4].…”
mentioning
confidence: 99%
“…Researchers in the field of experimental NEC have demonstrated that stem cells are beneficial in therapy for this condition [3,5,20,21]. The question remains as to how these cells are workingwhether it is by paracrine effects or by integration into the damaged tissue with regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple animal studies have demonstrated improved intestinal architecture with stem cell therapy, often directly injected into the peritoneal cavity [5,6]. Inhibiting the paracrine action of H 2 S in these cells is novel and demonstrates that release of this gasotransmitter is a possible mechanism for intestinal protection.…”
Section: Accepted Manuscript 10mentioning
confidence: 99%
See 1 more Smart Citation